The Influence of the Quality of Physical Assets of Geosite Stone Tourist Destinations on Visitor Satisfaction - Lestari, Melly Silvia; Setyowati, Tri; Fadjarwati, Nurlaila (Politeknik Negeri Bandung, 2025)
The Stone Garden Geosite is a geotourism destination in West Bandung Regency, boasting physical assets in ancient rock formations dating back over 27 million years. Despite its unique geological appeal, the number of visits to this tourist destination has declined in the past three years, from 110,434 visitors in 2021 to around 80,000 in 2023. The suboptimal quality of physical assets is suspected of influencing this decline. Preliminary observations revealed various issues, including limited accommodation, minimal recreational facilities, poorly maintained educational materials, inadequate prayer rooms, limited toilet facilities, and weak internet connections. This study aims to determine the effect of physical asset quality on visitor satisfaction using the dimensions of physical, accommodation, supporting facilities, and infrastructure. This study employed a quantitative descriptive method with an associative approach. Data were obtained through observation, interviews, and questionnaires with 114 respondents using a purposive sampling technique. Analysis was conducted through validity, reliability, normality, and simple linear regression tests using SPSS version 30. The results showed an R² value of 65,4%, indicating that physical asset quality significantly influences visitor satisfaction.